The implementation model of administrative reform with learning approach - Abbas Monavvarian (مدیریت دولتی, 2015)
Abstract: In regard to the policy implementation, there are a few research at global level and differences about implementation model are very high. In this research, a missing ring, i. e., enhancement of capabilities and competencies of implementers of policy through policy learning is under consideration. The research approach is based on quality research and grounded theory method. The population is experts who have been interviewed through theoretical sampling by deep interviews. In this method the researcher with a deductive approach and by the use of data prepares a reliable policy making theory. So after open coding, concepts and categories are extracted & will be put under the core category, causal conditions, context, intervening conditions and action and reaction strategies. Accordingly the main phenomenon is “policy learning”, and administrative system with characteristics such as “agility, quality and cheep public services, availability of services to the citizens, people’s satisfaction and satisfaction of employees” are the goals of the model. Also, based on force field theory, barriers and facilitator factors are identified.